2008
DOI: 10.1123/pes.20.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Program Reduces Anger Expression among Overweight Children

Abstract: This study tested the effect of a structured aerobic exercise program on anger expression in healthy overweight children. Overweight, sedentary children were randomly assigned to an aerobic exercise program or a no-exercise control condition. All children completed the Pediatric Anger Expression Scale at baseline and posttest. Anger Out and Anger Expression scores were lower for the exercise condition at posttest. Fitness improvements contributed significantly to final models, and points earned for adherence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
(45 reference statements)
2
17
0
1
Order By: Relevance
“…self-reported or parent-reported questionnaires) (Gee 2014; Goldfield 2012; Muzaffar 2014; Naar-King 2016; Pentz 2011; Salmoirago-Blotcher 2015; Smith 2015; Wong 2016). …”
Section: Resultsmentioning
confidence: 99%
“…self-reported or parent-reported questionnaires) (Gee 2014; Goldfield 2012; Muzaffar 2014; Naar-King 2016; Pentz 2011; Salmoirago-Blotcher 2015; Smith 2015; Wong 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Two studies used in‐class PA programs that were not combined with an academic lesson . Other interventions included recess or an after‐school program . Two studies included measurements of physical fitness changes in addition to academic behavior outcomes …”
Section: Resultsmentioning
confidence: 99%
“…Other interventions included recess or an after‐school program . Two studies included measurements of physical fitness changes in addition to academic behavior outcomes …”
Section: Resultsmentioning
confidence: 99%
“…For most of these children, a graded treadmill test, MRI scans of abdominal adipose tissue, measures of academic achievement, and teacher ratings of behavior were available (see Table 1). Methods and trial results have been reported (Bassali et al, 2010; Davis and Lambourne, 2009; Davis et al, 2007, in press; Meléndez-Ortega et al, 2010; Petty et al, 2009; Tkacz et al, 2008). …”
Section: Methodsmentioning
confidence: 99%